A simulation study of the effects of antibiotic treatment practices on the within-herd spread of contagious bovine pleuropneumonia in mixed crop-livestock system in Ethiopia - Lesnoff, Matthieu; Bonnet, P.; Laval, G.; Abdicho, S. (2005)
Contagious bovine pleuropneumonia (CBPP) is a respiratory disease of cattle caused by Mycoplasma mycoides subsmycoides small colony. CBPP is a major cause for concern for African countries because of the associated mortality, production losses and cost of its control. Despite OIE's disapproval, antibiotic treatments are commonly used in the field to control CBPIn this study, a stochastic simulation model was used to assess the impact of variability of the farmer treatment practices (delay in treatment after the observation of the initial clinical symptoms and proportion of treated animals among clinical cases) on the cumulative clinical incidence in CBPP-infected herds. Data were collected and analysed (previously to this study) from an Ethiopian highlands cattle-smallholder system (Boji district, West Wellega Zone), where local veterinary services reported prevalence of CBPP in the area and a research program was set up to estimate the epidemiological parameters of infection spread. The simulation results revealed the need for better promoting and disseminating of good medical practices on the use of antibiotics to farmers in order to ensure the attainment of the expected effectiveness of the treatment at the herd level.